Effect of Repeated Application of Switching Electric Field on Al/Ba0.9Sr0.1TiO3/Pt/Si and Al/Ba0.3Sr0.7TiO3/Pt/Si Thin Films - Lahiry, S. (Journal of Scientific Research, 2023)
Repeated application of switching the electric field on the electrical properties of the films, such as variation of capacitance with voltage and leakage current, were studied on thin films of Al/Ba0.9Sr0.1TiO3/Pt/Si (BST-0.9) and Al/Ba0.3Sr0.7TiO3/Pt/Si (BST-0.3) prepared by sol-gel method. The ferroelectric BST-0.9 films that exhibited degradation by applying a switching electric field showed hysteresis. Paraelectric BST-0.3 films did not show any degradation on repeated application of switching electric field. The resistivity, breakdown field, and Devonshire thermodynamic coefficient C3 were calculated for all the films. These physical properties are essential in choosing a film for particular applications such as memory, dynamic random access memory, tunable phase shifter, photodiodes in light sensors, etc.